Oценка эффективности системы администрирования единого социального взноса в Украине - Зорий, О.Г.; Друзин, Р.В.; Османова, Э.У. (Культура народов Причерноморья, 2013)
В статье рассмотрены общие основы начисления и уплаты единого социального взноса в Украине и проведен анализ эффективности системы его администрирования. Также определены факторы, влияющие на размер единого социального взноса и динамика их поступлений в течение 2011 – 2012 годов. Проанализированы особенности проведения проверок плательщиков взносов Пенсионным фондом Украины и его территориальных органов. Определена взаимосвязь между количеством проводимых документальных проверок Пенсионным Фондом Украины и размером поступлений единого социального взноса. Ключевые слова: единый социальный взнос, Пенсионный фонд, социальное страхование. У статті розглянуто загальні основи нарахування і сплати єдиного соціального внеску в Україні та проведено аналіз ефективності системи його адміністрування. Також визначено фактори, що впливають на розмір єдиного соціального внеску та динаміка їх надходжень протягом 2011 - 2012 років. Проаналізовано особливості проведення перевірок платників внесків Пенсійним фондом України та його територіальних органів. Визначено взаємозв'язок між кількістю проведених документальних перевірок Пенсійним Фондом України та розміром надходжень єдиного соціального внеску. Ключові слова: єдиний соціальний внесок, Пенсійний фонд, соціальне страхування. The article deals with the general principles of calculation and payment of the unified social tax in Ukraine. Determine the value of a single social contribution to the social protection system. The essence of a single social contribution, the feasibility and benefits of its implementation in the insurance system in Ukraine. It is shown that the introduction of a single social contribution is much easier life employers and entrepreneurs in charge of the administration and payment of pension and social security. The characteristic of the Law of Ukraine on single social tax. Determined that the benefits of introducing a single social contribution include the increase in revenues to social funds. The analysis of the effectiveness of the control system for the calculation and payment of a single social contribution in Ukraine. The factors that influence the size of a single social contribution and the dynamics of their revenue during the 2011 - 2012 period. The features of audits of contributors by the Pension Fund of Ukraine and its territorial bodies. The basic violations of the laws of contributors. Defined the relationship between the number of inspections carried out by the documentary Pension Fund of Ukraine and the size of a single social contribution receipts. Keywords: single social contribution, pension fund, social insurance.